Principles, problems and perspectives of Islamic banking - Volker Nienhaus (Intereconomics, 1985)
Since the late 1970s, financial institutions (banks, investment companies, insurance companies) have grown up in many countries in the Moslem world with the intention of conducting their business in accordance with Islamic, or Shariah, law. Above all else, this means business involving no interest payments. The following article explains the most important principles of Islamic banking and outlines some of the problems which appear to be most central to this sphere.
Keywords: 330; Islamic Banking